PROSPECTS OF THE USE OF THREONINE IN THE FEEDING OF BREEDING HENS OF DOMESTIC BREEDING - Гончаренко, О. М. (Scientific Progress & Innovations, 2013)
Introduction to the wheat-corn-soybean feed during rearing (18–23 weeks) and the maintenance of breeding chickens (24–51 weeks) L-threonine to the level of 0.60 and 0.63% significantly increased body weight – 5, 4%, egg production – by 5.5%, the fertilized eggs – by 1.1%, the birth of chickens – by 2.4%, the number of hatching eggs – by 6.7% and reduces the cost of feed for 10 hatching eggs by 6.6